ESTABLISHING INTERPERSONAL COMMUNICATION AND ORGANIZATIONAL CLIMATE TO IMPROVE WORK MOTIVATION - Arief Rokhman WONODIPHO (Journal of Education and Leadership in Education, 2019)
The research aims to obtain information about and to analyze the influence of: (1) interpersonal communication on work motivation, (2) organizational climate on work motivation, and (3) interpersonal communication on organizational climate. The study used a causal survey method, with path analysis technique. Population of 253 teachers sampled to 72 teachers. Data were gathered by using five-scaled questionnaires. The result of the research shows: 1) there is a direct influence of interpersonal communication on the motivation indicated by path coeficient of 0.468; 2) there is a direct influence of organizational climate on motivation indicated by path coeficent 0.447; 3) there is a direct influence of interpersonal communication on organizational climate indicated by path coefient of 0.735. The implication, improved interpersonal communication and organizational climate increase work motivation.